Interaksi Edukatif dalam Al-Qur`an - Alimuddin Alimuddin (Institut Agama Islam Negeri Palopo, 2018)
This research aims at analysing the interactive education concept in Qur’an wich examines specifically surah al-Baqarah (2) verse 133 and surah al-Saffat (37) verse 102. This research applied both qualitative research approach and are uses type of research literature (Library Research). The technique of data collection carried out in this Reseach was decomentation techniques. Furthermore, the collected data was analysed by using the content Analysis Method. The finding shows that educative interaction in the koran has purposes of promoting a generation of monotheism (Tauhid) to Allah, diligent in worship, and noble character. The achievement is significantly influenced by the personality influenced by the personality of an educator who is patient, caring, and knows the students’ psychology. Moreover, an educative interaction within Qur’an to correspond between values, knowledge and behavior wich lead the learners to be great figures, being able to build a mindset namely scientific thought and noble character.